Should Eligible Patients with T-Cell Lymphoma Receive High-Dose Therapy and Autologous Stem Cell Transplant in the Upfront Setting? - Casulo, Carla (2010)
Peripheral T-cell lymphomas (PTCL) are rare and aggressive subtypes of non-Hodgkin’s lymphoma. Compared to B cell lymphomas, the immunologic phenotype of PTCL portends a poorer prognosis, with the exception of anaplastic large cell lymphoma bearing the anaplastic lymphoma kinase protein. Patients with PTCL tend to present clinically in advanced disease states, show lower response rates to chemotherapy, and suffer from more frequent relapses and shorter remissions. The rarity of these lymphomas has made it difficult to carry out prospective, randomized trials delineating optimal treatments. Conventional and intensified chemotherapy have led to reasonable responses, but in many studies, frequent relapses. Consequently, high-dose chemotherapy and autologous stem cell transplantation (ASCT) have been actively studied in both the relapsed and upfront setting. In addition, the impact of disease status at transplantation is being investigated, though the optimal disease state at transplant is still a matter of debate, as is the timing of transplant. This article seeks to review the literature on the role of ASCT in PTCL, as well as to clarify what may be the optimal disease state in which to offer patients with PTCL autologous transplantation, if at all.